2021
DOI: 10.3390/molecules26020297
|View full text |Cite
|
Sign up to set email alerts
|

Using a B-Phycoerythrin Extract as a Natural Colorant: Application in Milk-Based Products

Abstract: Nowadays, there is a growing interest in finding new coloring molecules of natural origin that can increase and diversify the offer of natural food dyes already present in the market. In the present work, a B-phycoerythrin extract from the microalgae Porphyridium cruentum was tested as a food colorant in milk-based products. Using spectroscopy and colorimetry, the extract was characterized and gave evidence of good properties and good stability in the pH range between 4.0 and 9.0. Coloring studies were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In addition, phycobiliproteins have potential as natural colorants to use in food, cosmetics, and pharmaceuticals, especially as substitutes for synthetic dyes, which are generally toxic or otherwise unsafe (Arad and Yaron 1992;Sinha et al 2011;Kaur et al 2019). Particularly, great importance has to be given to C-phycocyanin (C-PC) because of its various medical and pharmacological properties, showing a therapeutic value thanks to its protective effect and anticarcinogenic 2019; Hsieh-Lo et al 2019;Niccolai et al 2019;Galetovic et al 2020;García et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phycobiliproteins have potential as natural colorants to use in food, cosmetics, and pharmaceuticals, especially as substitutes for synthetic dyes, which are generally toxic or otherwise unsafe (Arad and Yaron 1992;Sinha et al 2011;Kaur et al 2019). Particularly, great importance has to be given to C-phycocyanin (C-PC) because of its various medical and pharmacological properties, showing a therapeutic value thanks to its protective effect and anticarcinogenic 2019; Hsieh-Lo et al 2019;Niccolai et al 2019;Galetovic et al 2020;García et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One example is Bphycoerythrin extracted from red microalgae (formed by phycoerythrobilin chromophore and protein) [70]. Studies conducted by García et al [71] indicated that B-phycoerythrin has the potential to be used as a food coloring substance in milk-based products as an alternative to synthetic dyes. Phycoerythrin could be an alternative to anthocyanins in food dyeing in pH values in which anthocyanins are no longer red.…”
Section: Tetrapyrrole Applicationsmentioning
confidence: 99%
“…Unlike chlorophyll, in which the chromophore tetrapyrrole ring is a closed macrocyclic ring, chelating Mg at the centre, in PE it is an open chain tetrapyrrole lacking a bound metal. Porphyridium marinum could be potentially used as a source of bioactive phycoerythrin protein for a wide range of applications in fluorescence spectroscopy, as a colour agent for milk-based products, and more widely in cosmetic and pharmaceutical applications [69].…”
Section: Pigmentsmentioning
confidence: 99%
“…The methyl ester can be blended with conventional diesel, typically in the range of 5-20%. The generated fatty acid methyl esters (FAMEs) are then separated from the glycerol by-product, washed to remove traces of catalyst, dried, and used as biodiesel [69]. Algal biodiesel has been generated from various species with Botryococcus braunii, Nanocholoropsis oculata, and Dunaliella salina showing oil yields >50% [117].…”
Section: Algal Oils and Biodiesel Productionmentioning
confidence: 99%